UPAYA MENINGKATKAN PEMAHAMAN PEMBUKUAN SEDERHANA MELALUI APLIKASI BUKU WARUNG PADA PELAKU UMKM DESA RIDOGALIH - Fiqry Caturitama, Rasyad; Putra, Purnama (An-Nizam, 2025)
Financial management is a fundamental aspect in ensuring the sustainability and enhancing the welfare of Micro, Small, and Medium Enterprises (MSMEs). However, field observations indicate that many MSME actors, particularly in Ridogalih Village, still lack an adequate understanding of the importance of simple and systematic financial recording and management. This issue often leads to difficulties in monitoring cash flow, calculating profits, and planning sustainable business development. To address this challenge, a socialization and training program was conducted focusing on the utilization of the BukuWarung application as a digital financial recording tool that is easy to use and suitable for the needs of small-scale MSMEs. The methods implemented in this community service activity included socialization on the importance of financial record-keeping, training on the use of the application, and continuous evaluation of participants’ levels of understanding and skills. The results of the activity revealed an improvement in MSME actors’ understanding of simple bookkeeping concepts, accompanied by enhanced skills in recording daily transactions using the BukuWarung application. Furthermore, participants became more accustomed to and comfortable with the use of digital technology to support efficient business management.This activity is expected to provide a significant contribution to strengthening the effectiveness of MSME financial management, enhancing business competitiveness, and expanding the number of small enterprises capable of sustainable growth in Ridogalih Village.